The impact of the COVID-19 pandemic on the oncology services demand in a middle-income setting with universal health insurance (Colombia Medica, 2022)
Aim:We analyze the impact of the COVID-19 pandemic on oncology service demand in a middle-income country with universal health coverage.Methods:We collected data from January 1st-2017, to December 31th-2021 at a reference center in Bogotá-Colombia regarding first-time consultations of cross-cutting services (clinical oncology, hematology, palliative care, radiation oncology); specialized multidisciplinary units (breast, prostate, lung, stomach); inpatient and outpatient systemic therapy; radiotherapy; oncology surgery; and bone marrow transplant. In addition, a descriptive time series analysis was performed, estimating monthly percent change and endemic channels.Results:Starting the confinement (April 2020), a general decrease in service demand was observed (R: -14.9% to -90.0%), with an additional but lower reduction in August 2020 coinciding with the first pandemic wave (R: -11.3% to -70.0%). Follow-up visits and ambulatory treatment showed no consistent reductions. New patients’ consultations for cross-cutting services had a speedy recovery (1 month), but clinical oncology, specialized units, and in-hospital treatment resumed more slowly. Only breast and stomach cancer showed a sustained reduction in early-stage disease. Women and older patients had a more significant reduction in service demand.Conclusion:Despite no changes in service supply, the confinement induced a significant reduction in service demand. Variations by cancer type, service type, and population demographics deserve careful consideration for a suitable response to the emergency. The speedy recovery and the absence of a significant decrease during subsequent waves of the pandemic suggest patient resiliency and a lower impact than expected in middle-income settings in the presence of universal health insurance.